EVALUASI KEPUASAN PASIEN BERDASARKAN ASPEK ADMINISTRASI, FASILITAS, DAN KOMPETENSI KLINIS DI KLINIK GIGI HEGAR MEDIKA KOTA PALEMBANG - Sabrina Auliya Hegar; Maria Gresela Mulia; Jihan Syahrani; Stella Maria Fidela Maringka (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Introduction: Patient satisfaction is widely regarded as a primary indicator of service success rather than merely a supplementary measure. This principle also applies to dental healthcare services. Patient satisfaction reflects not only the outcomes of clinical treatment but also the quality of the relationship and communication between patients and healthcare professionals. Oral and dental health plays a vital role in supporting essential functions such as eating, speaking, and aesthetics, all of which significantly influence an individual’s overall quality of life. Therefore, efforts to improve service quality form the foundation for building patient trust and satisfaction in dental clinics. Service quality is assessed not only through the success of clinical procedures but also through non-clinical elements such as the friendliness of healthcare staff, the cleanliness of the clinic environment, the comfort of the facilities, and the accuracy and clarity of the information provided. This study aims to analyze the level of patient satisfaction with service quality at a dental clinic. The focus of the research is directed toward evaluating both clinical and non-clinical service components that may influence patients’ perceptions of overall service quality. Methods: This study involved 305 respondents selected using a purposive sampling technique. Data were collected through a questionnaire employing a 5-point Likert scale and analyzed using PLS-SEM with SmartPLS 4.0 software. Results:The findings indicate that scheduling and administration, clinic environment and facilities, as well as nurse quality and dentist competence, have a significant positive effect on recommendations and global satisfaction, with an R-square value of 0.673. Analysis of the measurement and structural models also confirms that all indicators used in this study are valid and reliable. Conclusion: Scheduling and administration, clinic environment and facilities, and nurse quality and dentist competence play a crucial role in enhancing patient recommendations and global satisfaction. Clinics are encouraged to strengthen non-technical service quality in accordance with the results of this study. These findings contribute to ongoing efforts to improve service quality within the primary healthcare sector.